Match analysis in Rugby Union: performance indicators of Rugby Championship and Super Rugby teams - Sella, F. S.; McMaster, D. T.; Serpiello, F. R.; La Torre, A. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: A number of key performance indicators (KPIs) have been found to discriminate between winning and losing performances in Rugby Union competitions. This study aimed to investigate the KPIs of winning and losing teams during recent Rugby Championship and Super Rugby seasons. METHODS: Data from 139 matches during the 2014-2015 Rugby Championship and 2015 Super Rugby were extracted from the SANZAAR website and retrospectively analyzed. Seventeen KPIs were used to describe the differences between winning and losing performances in different aspects of the game. Magnitude-based inferences, effect size with 90% confidence interval, percentage changes, and statistical significance were calculated. RESULTS: Winning teams during the Rugby Championship were most likely to score more tries, and very likely to gain more meters, beat more defenders, and miss less tackles compared to losing teams. In Super Rugby, winning teams were most likely to score more tries, execute more clean breaks, kicks in play and very likely to win more turnovers and concede a lower number of turnovers. The number of tackles made, and meters gained were also likely higher in Super Rugby winning teams compared to the losing counterparts. CONCLUSIONS: A limited number of KPIs differentiated were observed between winning and losing performances in the Rugby Championship, whereas numerous attacking and defensive KPIs were found to discriminate between winning and losing teams during Super Rugby. The method of data extraction, analysis and interpretation used herein could assist with game strategies and in turn better prepare teams and players for competition.